Pengaruh Employee Engagement Terhadap Value Added Pada Sekolah Papua Kasih - Muraram, Allan; Falah, Syaikhul; Daat, Sylvia C. (Fakultas Ekonomi, Universitas Cenderawasih, 2021)
This study is an element to prove whether there is an influence between what forms employeeinvolvement, namely enthusiasm, dedication, and partial absorption of added value and to examinethe effect of these elements simultaneously. The population in this study were employees at thePapua Kasih School, which is located in Jayapura. The sampling technique in this research is non-probability sampling with the technique of determining the sample being purposive sampling. Thenumber of questionnaires that can be processed and analyzed is 60 respondents. Data analysisusing multiple linear regression equations. The results showed that: vigor had a significant effect onvalue-added, dedication had a significant effect on value-added, and absorption had no significanteffect on value-added, while simultaneously all three had a significant effect on value-added.